Safety and Clinical Value of Prophylactic Ureteral Stenting Before Cytoreductive Surgery With Hyperthermic Intraperitoneal Chemotherapy. Issue 5 (May 2023) - Hanna, David N.; Hermina, Andrew; Bradley, Emma; Ghani, Muhammad O.; Mina, Alexander; Bailey, Christina E.; Idrees, Kamran; Magge, Deepa
Background: Prophylactic ureteral stents (PUS) are typically placed prior to complex abdominal or pelvic operations at the surgeon's discretion to help facilitate detection of iatrogenic ureteral injury. However, its usefulness and safety in the setting of cytoreductive surgery with hyperthermic intraperitoneal chemotherapy (CRS-HIPEC) have not been examined. This study aims to evaluate the potential clinical value and risk profile of prophylactic ureteral stent placement prior to CRS-HIPEC. Methods: We performed a single-institutional retrospective analysis of 145 patients who underwent CRS-HIPEC from 2013 to 2021. Demographic and operative characteristics were compared between patients who underwent PUS placement and those that did not. Ureteral stent–related complications were evaluated. Results: Of the 145 patients included in the analysis, 124 underwent PUS placement. There were no significant differences in patient demographics, medical comorbidities, or tumor characteristics. Additionally, PUS placement did not significantly increase operative time and was not associated with increased pelvic organ resection. However, patients who underwent prophylactic ureteral stenting had significantly higher peritoneal carcinomatosis index score (15.1 vs 9.1, P = .002) and increased rate of ureteral complications (24.2% vs 14.3%, P = .04), which led to lengthened hospital stay (13.2 days vs 8.1 days, P = .03). Notably, the sole ureteral injury and three cases of hydronephrosis were seen in patients who underwent PUS. Conclusion: Prophylactic ureteral stent placement in patients undergoing CRS-HIPEC may be useful, particularly in patients with predetermined extensive pelvic disease. However, PUS placement is not without potential morbidity and should be selectively considered in patients for whom benefits outweigh the risks.